ASUHAN KEPERAWATAN PADA AN.N DENGAN DIARE CAIR AKUT (DCA) DI RUANG SERUNI RSUD KABUPATEN MUNTILAN - Krismawati, Irma; Wuulansari, Ajeng Dewi; Hastuti, Tulus Puji (Viva Medika, 2020)
Diarrhea is a disease caused by the environment. It is still the biggest health problem in Indonesia due to poor condition of resources, environment and people's behavior to live a clean and healthy life. If diarrhea is defined as a condition, abnormal bowel movements that are more than 3 times a day with a consistency of liquid stool can be accompanied by blood or mucus. The research objective was to describe the management of pediatric nursing care with a focus on the study of acute liquid diarrhea. This research is a field research (field research) using a qualitative descriptive approach. The results of this study indicate a significant result of intervention through the client's family which has a great influence on the client's care and recovery.